Bibliometric Analysis of Green Finance and Sustainable Investment Strategies - Judijanto, Loso; Yoga, Tirta; Wijayanti, Indah Oktari (West Science Social and Humanities Studies, 2024)
Green finance and sustainable investment strategies have gained significant attention as key mechanisms to address global environmental challenges and drive sustainable development. This study employs bibliometric analysis to explore the thematic, geographical, and temporal trends in research on green finance and sustainable investments, using data from the Scopus database. The findings reveal that central themes, such as "sustainability," "green economy," and "investments," dominate scholarly discourse, with growing emphasis on emerging topics like "green technology innovation" and "decentralized finance." China, the United Kingdom, and European nations are identified as leading contributors to research in this field, with notable collaborations across regions. However, disparities in regional representation and challenges such as inconsistent ESG frameworks and perceived financial risks hinder the adoption of green finance globally. The study highlights opportunities for harmonizing global standards, leveraging technological innovations, and expanding research in underrepresented regions. These insights provide valuable guidance for policymakers, financial institutions, and researchers aiming to enhance the effectiveness of green finance and sustainable investments.